Tobacco use and mortality due to cardiovascular disease, malignancyand allcauses in a large cohort - Liaquat Roopesh Johnson; Rangaswamy Siddaiah (International Journal of Medical Research and Review, 2016)
Introduction: 67.6% of all Non-Communicable Disease (NCD) deaths are attributable to Cardiovascular Diseases (CVDs) and Cancers. Of the 14.2 million annual deaths attributable to modifiable behavioural factors, tobacco use accounts for 6 million (42.2%). This study aims to determine the relationship between tobacco use and mortality due to cardiovascular diseases (CVDs), malignancy, and all-causes among adults (>18 years) in the US.Materials and Methods: A cohort of 96164 adults with data on tobacco use was selected from the public-use dataset of the US National Longitudinal Mortality Study (NLMS). The various forms of tobacco use- smoking, smokeless, both smoking and smokeless- were examined in relationship to specific-cause and all-cause mortality.Results: In bivariate analyses age category and sex were identified as possible confounders. Separate analyses were performed for CVD mortality, cancer mortality and all-cause mortality. Factors that reached statistical significance were subjected to multivariate analyses. Apart from age category, daily cigarette smoking was significantly associated with both cancer and CVD mortality (p: <0.0001). There was a statistically significant relationship between age category, sex, any tobacco use and all-cause mortality (p: <0.0001).Conclusions: CVD and cancer mortality in the US are significantly associated with daily cigarette smoking. All-cause mortality in the US is associated with any tobacco use.